Effects of Nutrition Intervention on Total and Cancer Mortality: 25-Year Post-trial Follow-up of the 5.25-Year Linxian Nutrition Intervention Trial. (3rd April 2018) - Wang, Shao-Ming; Taylor, Philip R; Fan, Jin-Hu; Pfeiffer, Ruth M; Gail, Mitchell H; Liang, He; Murphy, Gwen A; Dawsey, Sanford M; Qiao, You-Lin; Abnet, Christian C
Abstract: Background: A beneficial effect of supplementation with selenium, vitamin E, and beta-carotene was observed on total and cancer mortality in a Chinese population, and it endured for 10 years postintervention, but longer durability is unknown. Methods: A randomized, double-blind, placebo-controlled trial was conducted in Linxian, China, from 1986 to 1991; 29 584 residents age 40 to 69 years received daily supplementations based on a factorial design: Factors A (retinol/zinc), B (riboflavin/niacin), C (vitamin C/molybdenum), and/or D (selenium/vitamin E/beta-carotene), or placebo for 5.25 years, and followed for up 25 years. Hazard ratios (HRs) and 95% confidence intervals (CIs) for the intervention effects on mortalities were estimated using Cox proportional hazards models. Results: Through 2016, the interventions showed no effect on total mortality. The previously reported protective effect of Factor D against total mortality was lost 10 years postintervention. The protective effect of Factor D for gastric cancer was attenuated (HR = 0.93, 95% CI = 0.85 to 1.01), but a newly apparent protective effect against esophageal cancer was found for Factor B (HR = 0.92, 95% CI = 0.85 to 1.00, two-sided P = .04). Other protective/adverse associations were observed for cause-specific mortalities. Protective effects were found in people younger than age 55 years at baseline against non–upper gastrointestinal cancer death for Factor A (HR = 0.80, 95% CI = 0.69 to 0.92) and against death from stroke for Factor C (HR = 0.89, 95% CI = 0.82 to 0.96). In contrast, increased risk of esophageal cancer was found when the intervention began after age 55 years for Factors C (HR = 1.16, 95% CI = 1.04 to 1.30) and D (HR = 1.20, 95% CI = 1.07 to 1.34). Conclusions: Multiyear nutrition intervention is unlikely to have a meaningful effect on mortality more than a decade after supplementation ends, even in a nutritionally deprived population. Whether sustained or repeat intervention would provide longer effects needs further investigation.